2019
DOI: 10.20429/ijsotl.2019.130305
|View full text |Cite
|
Sign up to set email alerts
|

Do Professions Represent Competence for Entry-to-Practice in Similar Ways? An Exploration of Competence Frameworks through Document Analysis

Abstract: Professional accrediting and regulating bodies are increasingly trying to delineate the knowledge and skills needed for entry-to-practice for quality assurance and international labor mobility. The purpose of this study was to compare how professions describe and represent competence. Current, publicly accessible Canadian entry-to-practice competence frameworks for ten professions (Medicine, Nursing, Occupational Therapy, Pharmacy, Psychology, Social Work, Teaching, Engineering, Law, and Planning) were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In contrast, programs taking a more competency-based approach appear to be more concerned with developmental use of assessment data to inform decisions about students' learning processes and products (i.e., outcomes). This may be because of their extensive workintegrated learning requirements (Rich, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, programs taking a more competency-based approach appear to be more concerned with developmental use of assessment data to inform decisions about students' learning processes and products (i.e., outcomes). This may be because of their extensive workintegrated learning requirements (Rich, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Given these differences, there is a need to also understand how entry-to-practice competence frameworks are being operationalized in postsecondary programs across professions. How a program operationalizes competency-based learning and assessment will likely depend on several factors, including: (a) the profession's pathway to licensure, (b) program requirements set by the professional accrediting body, (c) how competence is conceptualized within the profession, (d) the vision of program leadership who make implementation decisions, (e) university regulations and policies, (f) the financial and human resources available to the program, and (g) faculty members' buy-in and know-how (Pérez et al, 2016;Rich, 2019).…”
mentioning
confidence: 99%
“…This concept of reducing duplication was also identified in the revision of the CanMEDS 2015 Physician Competency Framework where Frank et al 2015 identified that "concepts that are relevant to multiple roles will be articulated in the role where they are most prominent" and that "the framework itself will avoid repetition" (2015, p. 6). In the competency literature however, this approach has been described as "reductionist thinking," that arises even when taking a holistic approach to assess a professional's performance across contexts, highlighting the tension that exists between conceptualising competence as a whole or as a summation of its components (Rich, 2019).…”
Section: Reducing Duplicationmentioning
confidence: 99%
“…These include a philosophical alignment between methods, underlying principles, contexts of practice and practice analysis, developing and implementing a plan of data collection and analysis that is methodologically defensible and fit-for-purpose, and an audit trail that can be examined by the intended community. How a profession conceptualizes competence (e.g., degree of granularity from atomistic to holistic/integrated) will influence how developers decide to represent competence in a framework (26). Developers will need to consider the level of granularity desired in the framework (22), balancing enhanced precision (atomistic) against competency in dynamic contexts (holistic) (22,27).…”
Section: Step 4 Translate and Testmentioning
confidence: 99%